BACTERIOLOGICAL PROFILE AND ANTIMICROBIAL SUSCEPTIBILITY IN DIABETIC FOOT ULCER PAITIENTS (Journal of Medical & Health Sciences Review, 2025)
Diabetic foot ulcers (DFUs) affect 5-10% of diabetic patients and often arise from neuropathy, vascular insufficiency, and impaired immunity, complicating wound healing. Recurrence risk factors include gender, smoking, diabetes duration, prior ulceration, peripheral artery disease, and painful diabetic neuropathy. DFUs are frequently colonized by polymicrobial infections, with increasing antimicrobial resistance complicating treatment. Hospital-based studies show higher prevalence rates of DFUs compared to population-based studies, with a notable prevalence in male patients and those with type 2 diabetes mellitus. This study aimed to determine the frequency of bacterial infections and evaluate antimicrobial susceptibility patterns in DFUs at a tertiary care hospital in Rawalpindi. A cross-sectional study over six months September 2024-Feburary 2025 involved collecting tissue samples (n=225) from DFU patients. Bacterial cultures were analyzed using standard microbiological techniques, and antibiotic susceptibility was tested via the Kirby-Bauer method. Among the 225 samples, 170 were from males, with a mean age of 56.4 years. The microbial profile revealed a polymicrobial composition, predominantly Pseudomonas aeruginosa (24.9%) and E. coli (21.5%) as the most common gram-negative pathogens, while Staphylococcus aureus (21.5%) was the most prevalent gram-positive pathogen. Antibiotic susceptibility testing indicated Pseudomonas aeruginosa had high sensitivity to Tobramycin (60.9%) and Ciprofloxacin (60%), but resistance to Cefixime (64.7%). E. coli showed high responsiveness to piperacillin-tazobactam (91.8%) and resistance to tetracycline (83%). Staphylococcus aureus exhibited sensitivity to Tobramycin (70.6%) but resistance to tetracycline (58.8%). The findings highlight the diverse microbial environment and antimicrobial resistance in DFUs, emphasizing the need for susceptibility testing to guide effective therapy and tailored management strategies for improved treatment outcomes.